PERTUMBUHAN IKAN NILA GESIT (Oreochromis Sp) YANG DIPELIHARA MEDIA DENGAN SALINITAS BERBEDA DAN PENGARUHNYA TERHADAP EFISIENSI PEMANFAATAN PAKAN, LAJU PERTUMBUHAN SPESIFIK (SGR) DAN PERTUMBUHAN BOBOT BIOMASSA - Nurcahyo Kursistiyanto Kursistiyanto (Jurnal DISPROTEK, 2016)
ABSTRACT The material used is a seed gesit tilapia weighing 6.15. ± 0.084. The research is experiments laboratory. Research using completely randomized design and three replications. The treatment salinity of water medium i.e. (0, 5, 10; 15;20 dan 25 permil). 45 day old gesit tilapia maintenance and variables taken this research : feed efficiency , specific growth rate and growth of biomass weight. Data were analyzed by analysis of variance (ANOVA). To know the difference in treatment was tested using the F test with SPSS program version 17. The results showed that the various salinity of water medium have more significant influence (p